Pengaruh pertumbuhan ekonomi terhadap derajat desentralisasi fiskal di Kabupaten Tanjung Jabung Timur - Amos Joan Ramon Lubis; Parmadi Parmadi; Siti Aminah (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This study aims to analyze: 1) the degree of fiscal decentralization in East Tanjung Jabung Regency as measured by the ratio of fiscal autonomy degrees, regional financial independence ratio and regional financial dependency ratio; 2) the effect of economic growth on the degree of fiscal decentralization of East Tanjung Jabung Regency. The data used are secondary data of Tanjung Jabung Timur Regency during the period 2001 - 2015. Data were analyzed descriptively using fiscal decentralization ratios and using simple linear regression models. The results of the study found: 1) The degree of fiscal autonomy and the regional financial independence ratio of the Tanjung Jabung Regency are classified as very low, while the regional financial dependency ratio is very high; 2) Economic growth has a significant and positive influence on the degree of fiscal autonomy and the financial independence ratio of the East Tanjung Jabung Regency. On the contrary it does not have a significant effect on the regional financial dependency ratio.